Electrical Energy Audit in Pakuwon City Mall 2 Building for Efficiency - Ade Kristanto; Saidah (Fakultas Teknik Universitas Bhayangkara, 2023)
This study conducted an electrical energy audit activity at the Pakuwon City Mall 2 (PCM2) Surabaya Building to determine the utilization of electrical energy in the electrical system which includes the type of energy, amount of energy used, energy equipment, energy intensity, load profile, the performance of energy equipment, Energy Saving Opportunities (ESOs) and value of Energy Consumption Intensity (ECI) in an air-conditioned room. From the calculation results is obtained that the value of ECI in the PCM2 Surabaya Building for an AC room is 8.231 kWh/m2/month and 98.772 kWh/m2/year and is included in the efficient criteria. Based on the research that has been done, it is known that most of the rooms in the PCM2 Surabaya Building have ideal room temperatures. The results of measuring the strong level of lighting in PCM2 Surabaya's rooms, most of the values met the standards set by SNI 03-6197-2000 and the results of measuring the quality of electric power in PCM2 Surabaya met the standards set by PLN.